On Wolves and Sheep : Exploring the Expression of Political Thought in Golden Age Spain. - Kahn, Aaron M. (Cambridge Scholars Pub., 2011)
With the rise of nationalism and with it he nation-state in the fifteenth and sixteenth centuries so arose new polemical issues. As the Spanish Empire expanded in the sixteenth century, theologians, jurists, artists and politicians commented on the morality and legitimacy of the imperial enterprise. With the increase in power of successive Spanish sovereigns from the Catholic Monarchs to Philip II (1556-98), followed by the decadence of the state through the reign of Charles II (1665-1700), p ...